The relationship between blood lipids and endometriosis: a cross-sectional study from NHANES (1999–2006) and a bidirectional Mendelian randomization study - Dingchuan Peng; Wei Zhong; Yiran Wang; Yiyao Fu; Wei Shang (Journal of Psychosomatic Obstetrics and Gynecology)
Objective Observational studies suggest a link between blood lipid levels and endometriosis risk, but clinical evidence is limited and causality has not been established. This study aims to clarify this relationship using NHANES data (1999–2006) and bidirectional Mendelian Randomization (MR) analysis.Methods We analyzed NHANES data to explore the relationship between blood lipids and endometriosis risk using multivariable logistic regression, nonlinear testing, and trend analysis. For causal inference, MR was performed using GWAS data from the UK Biobank (lipid levels) and the Finnish Endometriosis Database (endometriosis).Results In NHANES (n=2,201), elevated triglycerides (TG) were significantly associated with increased endometriosis risk (OR, 2.10; 95% CI, 1.00–3.49; p < 0.05). MR analysis confirmed this association (OR, 1.19; 95% CI, 1.07–1.32; p < 0.006) and suggested HDL may protect against endometriosis (OR, 0.79; 95% CI, 0.63–0.99; p < 0.05). Additionally, bidirectional MR indicated that endometriosis may also contribute to TG dysregulation (OR, 1.02; 95% CI, 1.01–1.03; p < 0.006).Conclusion Our findings suggest that elevated TG levels may increase endometriosis risk, while HDL may provide a protective effect. These results offer new insights and may inform future management strategies for endometriosis. However, large-scale longitudinal studies are needed to further validate these associations.